MSME Digital Transformation: Implementing Big Data-Based Marketing Strategies to Improve Competitiveness - Deden Komar Priatna; Anne Lasminingrat; Dety Sukmawati (Unram Journal of Community Service, 2025)
Ma Utik MSME, located in Cilembu Village, Sumedang Regency, is one of the Cilembu sweet potato processing businesses that has great potential in supporting the village economy. However, low digital literacy, manual business management systems, limited market distribution, and a lack of product innovation are obstacles to increasing competitiveness amid increasingly fierce competition. This community service program aims to carry out digital transformation through the application of big data-based marketing strategies to strengthen management capacity and expand the market reach of MSMEs. The implementation method is carried out participatively through socialization, digital literacy and business management training, implementation of digital technology (Google Analytics, social media insights, and simple CRM), as well as intensive mentoring and periodic evaluations. The results of the activities showed a significant increase in digital literacy and business management, with participants' comprehension scores reaching 88-90% of the maximum score, particularly in the areas of digital financial recording, stock management, and business planning. In the field of marketing, there was a threefold increase in the consistency of social media posts, a 150% increase in engagement, and the use of marketplaces that generated an average of ten transactions per month. Partners also succeeded in building a customer database with a minimum of 50 active entries used for retargeting promotions, thereby strengthening customer retention. Product and packaging innovations were also produced, in the form of two new variants and three packaging designs with longer durability, which increased the selling value and branding of local products. The socio-economic impact can be seen from the 60% increase in average monthly income, the expansion of market reach from local to regional, and the multiplier effect through the adoption of digitalization by other MSMEs around Cilembu Village. In conclusion, this program successfully demonstrates that big data-based digital transformation can improve management efficiency, expand markets, and drive product innovation, thereby strengthening the competitiveness of MSMEs while supporting sustainable village economic development. Keywords: MSMEs, digital transformation, big data, digital marketing, competitiveness